Media policy for private media in the age of digital platforms. (August 2019) - Enli, Gunn; Raats, Tim; Syvertsen, Trine; Donders, Karen
Digital platforms such as Google, Facebook and Netflix have caused a watershed moment not only for markets and businesses but also for media policy. Concerns about the US-based digital platforms' impact on national media markets have grown among European media businesses as well as policy makers. Media policy research argues that small media markets are particularly vulnerable to global players and foreign influence, but that market size must be understood also in the context of political traditions. This article investigates how digital platforms influence media policy for private media businesses in the small media systems of Norway and Flanders. Drawing on 20 qualitative interviews with CEOs and top-level media managers in these two small media markets, we ask what private media businesses expect from policy makers in light of the intensified competition from digital platforms, what experience they have with cooperating with policy makers and what explains the differences between Norway and Flanders. A key finding is that the managers in both markets want policy makers to regulate digital platforms to secure level playing field, and that the Norwegian respondents had more positive experiences with co-regulation and expressed more trust in policy makers and policy instruments, compared to the Flemish. Despite the global players and the need for transnational solutions, regional variations in policy making still matters, and might inform the discussion about how to regulate the digital platforms.